Microglia and Astrocyte Activation by Toll-Like Receptor Ligands: Modulation by PPAR-γ Agonists - Catherine Gurley; Jessica Nichols; Shuliang Liu; Nirmal K. Phulwani; Nilufer Esen; Tammy Kielian (PPAR Research)
Microglia and astrocytes express numerous members of the Toll-like receptor (TLR) family that are pivotal for recognizing conserved microbial motifs expressed by a wide array of pathogens. Despite the critical role for TLRs in pathogen recognition, when dysregulated these pathways can also exacerbate CNS tissue destruction. Therefore, a critical balance must be achieved to elicit sufficient immunity to combat CNS infectious insults and down-regulate these responses to avoid pathological tissue damage. We performed a comprehensive survey on the efficacy of various PPAR-γ agonists to modulate proinflammatory mediator release from primary microglia and astrocytes in response to numerous TLR ligands relevant to CNS infectious diseases. The results demonstrated differential abilities of select PPAR-γ agonists to modulate glial activation. For example, 15d-PGJ2 and pioglitazone were both effective at reducing IL-12 p40 release by TLR ligand-activated glia, whereas CXCL2 expression was either augmented or inhibited by 15d-PGJ2, effects that were dependent on the TLR ligand examined. Pioglitazone and troglitazone demonstrated opposing actions on microglial CCL2 production that were TLR ligand-dependent. Collectively, this information may be exploited to modulate the host immune response during CNS infections to maximize host immunity while minimizing inappropriate bystander tissue damage that is often characteristic of such diseases.